2015
DOI: 10.1051/0004-6361/201525980
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind sputtering of dust on the surface of 67P/Churyumov-Gerasimenko

Abstract: Aims. Far away from the Sun, at around 3 AU, the activity of comet 67P/Churyumov-Gerasimenko is low and changes with local time (solar insolation), with location (chemical heterogeneity of the surface), and with season. When the activity is very low because the total cross section of the comet against the Sun is small, the solar wind has access to the surface of the comet and causes ion-induced sputtering of surface material, which we wish to observe. Methods. We used the Double Focussing Mass Spectrometer (DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 38 publications
3
73
1
Order By: Relevance
“…They measure the strongest emissions for late 2014 at northern sub-spacecraft latitudes. Wurz et al (2015) report highest abundances of neutral H 2 O for northern (positive) latitudes in the coma of 67P. Those measurements were performed with the ROSINA-DFMS mass spectrometer during several days along a bound orbit at ≈10 km distance from the nucleus.…”
Section: Heterogeneity Effectsmentioning
confidence: 99%
“…They measure the strongest emissions for late 2014 at northern sub-spacecraft latitudes. Wurz et al (2015) report highest abundances of neutral H 2 O for northern (positive) latitudes in the coma of 67P. Those measurements were performed with the ROSINA-DFMS mass spectrometer during several days along a bound orbit at ≈10 km distance from the nucleus.…”
Section: Heterogeneity Effectsmentioning
confidence: 99%
“…Sputtering of dust refractory material from the surface of 67P (Wurz et al 2015) is observed. When Rosetta was 10 km from the comet in mid-October 2014, DFMS observed nonvolatile refractory species (Na, K, Si, and Ca) in the coma.…”
Section: Conditions At the Comet From Octobermentioning
confidence: 92%
“…At such low outgassing rates, the solar wind, while deflected because of pickup of cometary ions, has access to the nucleus. The non-volatile neutrals in the coma (see, Wurz et al 2015) are evidence of solar wind sputtering of these neutrals from the comet surface. Since the solar wind threads the entire neutral coma (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such surface production mechanisms have not been considered in models of cometary comae. We note that water ion-surface collisions may also contribute to the observed sputtering of other surface species, such as refractory elements (Wurz et al 2015).…”
Section: Discussionmentioning
confidence: 99%